Leveraging Jamming to Help Drones Complete Their Mission - Pietro Tedeschi (16864164) (2019)
We propose JAM-ME, an autonomous jamming-assisted navigation system that allows a drone to accomplish its mission even in the presence of an anti-drone jamming protection system. In this contribution, we review the current state-of-the-art highlighting how current solutions to respond to drones are completely ineffective against JAM-ME. In particular, we introduce our solution and its theoretical framework, and later we relax a few constraints of the baseline model (adding wind drift, and allowing the target to be randomly placed within the jammed area). Moreover, we run extensive simulations that do support our findings: even under the combined action of jamming and wind drift, the drone can reach a target randomly deployed in the jamming area-any other drone, under the same conditions, would have simply failed. As per the overhead, under very conservative assumptions, JAM-ME experiences an average overhead of 70%; however, note that such overhead can be reduced by at least a tenfold factor in practical settings-discussed in the paper. Finally, we highlight the intrinsic limitations of our solution, potential countermeasures, and new jamming strategies that can pave the way to further research. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2019.2963105